Antiparasitic potential of Nephrolepis biserrata methanol extract against the parasitic leech Zeylanicobdella arugamensis (Hirudinea) and LC-QTOF analysis - Muhammad Dawood Shah; Balu Alagar Venmathi Maran; Fatin Khairah Haron; Julian Ransangan; Ching Fui Fui @ Faihana Ching Abdullah; Sitti Raehanah Muhamad Shaleh; Rossita Shapawi; Yoong Soon Yong; Susumu Ohtsuka (Nature Publishing, 2020)
Marine leech Zeylanicobdella arugamensis (Piscicolidae), an economically important parasite is infesting predominantly cultured groupers, hybrid groupers and other fsh in Southeast Asian countries. In this study, we tested the anti-parasitic potential of a medicinal plant Nephrolepis biserrata found in Sabah, East Malaysia against Z. arugamensis. Various concentrations of methanol extracts of the plant were tested experimentally against Z. arugamensis and disinfestation of the leech from its primary host hybrid groupers. The composition of methanol extract of N. biserrata was determined through LC-QTOF analysis. The signifcant anti-parasitic activity of 100% mortality of leeches was observed with the exposure of N. biserrata extracts. The average time to kill the leeches at concentrations of 25, 50 and 100 mg/ml was 25.11 ± 3.26, 11.91 ± 0.99, and 4.88 ± 0.50 min., respectively. Further, at various low concentrations of N. biserrata 2.5, 5 and 10 mg/ml, hybrid groupers were disinfested in an average time of 108.33± 12.65, 65.83 ± 9.70 and 29.16 ± 5.85 min., respectively. The tandem mass spectrometry data from LC-QTOF indicated some hits on useful bioactive compounds such as terpenoids (ivalin, isovelleral, brassinolide, and eschscholtzxanthin), favonoids (alnustin, kaempferol 7,4′-dimethyl ether, and pachypodol), phenolics (piscidic acid, chlorogenic acid, and ankorine), and aromatic (3-hydroxycoumarin). Thus N. biserrata can act as a potential biocontrol agent.